The Role of Plant-Associated Bacteria, Fungi, and Viruses in Drought Stress Mitigation - Poudel, Mousami; Mendes, Rodrigo; Costa, Lilian A. S.; Bueno, C. Guillermo; Meng, Yiming; Folimonova, Svetlana Y.; Garrett, Karen A.; Martins, Samuel J. (Frontiers in Microbiology, 2021)
Drought stress is an alarming constraint to plant growth, development, and productivity worldwide. However, the use of plant-associated organisms is an eco-friendly approach that can enhance stress resistance. Plant-associated bacteria, fungi, and viruses, such as bacteria and fungi, induce various mechanisms to cope with the negative impacts of drought, which involve plant biochemical and physiological changes. These mechanisms include osmotic adjustment, antioxidant enzyme enhancement, modification in phytohormonal levels, biofilm production, increased water and nutrient uptake as well as increased gas exchange and water use efficiency. Production of microbial volatile organic compounds (mVOCs) and induction of stress-responsive genes by microbes also play a crucial role in the acquisition of drought tolerance. This review offers a unique exploration of the role of plant-associated microorganisms – plant growth promoting rhizobacteria and mycorrhizae, viruses, and their interactions – in the plant microbiome (or phytobiome) as a whole and their modes of action that mitigate plant drought stress.